Socio-Cultural Content in English Textbook: A Teachers' Perspective - Ery Ryan Nirwana; Ika Lestari Damayanti (LINGUISTICA, 2025)
Socio-cultural content in textbooks help EFL teachers to prepare students to be global and local English speakers. Therefore, the proportion of the socio-cultural aspect in English textbooks should be distributed appropriately, whether local or intercultural. This study aims to understand Indonesian English teachers’ perspective on the socio-cultural content in English textbooks. This study is a mixed- method case study, involving 15 experienced English teachers. The data is collected through a questionnaire, distributed through WhatsApp by adhering to convenient sampling techniques. Data were analyzed following descriptive statistics and thematic analysis. This study highlights the critical role of cultural education in English language teaching, underscoring its functions in enhancing linguistic proficiency and also fostering intercultural competence. Participants recognize the value of integrating both local and intercultural content, with a strong preference for locally relevant materials that resonate with students' cultural backgrounds. However, this study also stresses the importance of flexibility in utilizing textbook materials. The researcher acknowledges that the limited number of participants hinders the ability to generalize the findings to a wider context. Future studies should involve more participants from a wider context and also investigate students' perspectives or conduct classroom observations to deepen the study's overall impact.